2017
DOI: 10.5751/es-09168-220151
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in ecosystem services in deprived urban areas: understanding people’s responses and consequences for well-being

Abstract: ABSTRACT. Urban commons are under pressure. City development has led to the encroachment and ecological degradation of urban open space. Although there is growing insight that urban ecosystems need to be protected, there is hardly any attention for the consequences (of both pressures and protection efforts) for vulnerable human population groups. We aim to understand how urban development affects the well-being of the urban poor, through shifts in ecosystem services (ES) and people's responses to these shifts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Overall, the most studied greening interventions were new greenways or parks (n = 9 [25,27,[35][36][37][38][39][40][41], whereas two focused on street greening [15,42] and three on environmental remediation, such as brownfield cleanup and redevelopment [27,42,43]. Two studies focused on more than one greening intervention, covering environmental remediation followed by either street greening [42] or the creation of new parks [27]. Among the 15 included studies, 12 focused on neighborhoods that experienced gentrification, at least in part, because of greening initiatives (i.e., green gentrification).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the most studied greening interventions were new greenways or parks (n = 9 [25,27,[35][36][37][38][39][40][41], whereas two focused on street greening [15,42] and three on environmental remediation, such as brownfield cleanup and redevelopment [27,42,43]. Two studies focused on more than one greening intervention, covering environmental remediation followed by either street greening [42] or the creation of new parks [27]. Among the 15 included studies, 12 focused on neighborhoods that experienced gentrification, at least in part, because of greening initiatives (i.e., green gentrification).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While greater exposure to green space can significantly lower the odds of poor health for residents of gentrifying neighborhoods, a study in New York found that only residents with a higher level of education and income appeared to benefit from this resource [44]. In a study focusing on Bangalore, India, respondents mentioned that the creation of parks allowed them to have walking paths, aesthetic improvements, and areas for children to recreate [27]. The increase in park access was linked with higher happiness and self-reported well-being for the wealthiest and middle-income residents [27].…”
Section: Self-reported Health and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural practices are changing with the introduction of new technologies for the remote monitoring and controlling of environmental conditions, such as intelligent sensors, robots, proximal/remote sensing [ 1 , 2 ]. These new technologies applied to agriculture are helping to meet the nutritional requirements of an increasing population, minimizing environmental impacts and coping with the scarcity of resource availability, also exacerbated by climate changes [ 3 ]. Part of this change is happening in urban areas, where over 54% of the world population is concentrated [ 4 ] and which consumes most of the world’s energy and resources while producing the majority of greenhouse gases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, values may change over time [18] and include both use values (e.g., irrigation) and non-use values (e.g., swimming and aesthetics) [14,19]. These multiple, personal and changing values of water are also discussed and reflected upon in the ecosystem services literature (see, e.g., [20][21][22]).…”
Section: Valuation Of Watermentioning
confidence: 99%